Strike the hammer : the Black freedom struggle in Rochester, New York, 1940-1970 - Hill, Laura Warren (Cornell University Press, 2021)
"This book explores the rise of the Black Freedom Struggle in Rochester, NY across the mid-twentieth century. It examines Black migration, politics, rebellions, organizing, and capitalism"--